THE LOCAL MEDIA OF NIŠAVA DISTRICT IN DIGITAL AGE: ECONOMIC POSITION OF LOCAL MEDIA - Vujović, Marija Z; Pavlović, Dragana Č; Obradović, Neven (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
The aim of the paper is to investigate the economic situation of the local media in the Niš district and the capacities of the local media market. The paper used research results obtained through in-depth interviews with editors of 20 local media. Some of the interlocutors are editors of publications or programs. The results of the survey confirm their poor economic situation. Most local media have problems in business, most often existential and human resources, and the local media market is small and poor.The results of the research show that half of the media have problems with staff, permanently or occasionally. The local media of the Nišava district lack journalists, cameramen and montagers. There are almost no big advertisers in the local media.However, more than half of the media from the sample have positive business results, while others "survive". Most media pay employees a minimum earnings or wages below the national average. All local commercial media use funds intended for project co-financing of public interest from city, municipal and republican budgets, but most of them are not satisfied with the funds received. Similar to the world, moving the public to the Internet where citizens are informed thanks to online media reduces the circulation, rating and income of local media in the Nišava district, but most of the interlocutors in our research pointed out that the biggest problem is the poor local media market.
Keywords: local media; media economy; journalism; media market; project co-financing